Depressive Symptoms, Chronic Diseases, and Physical Disabilities as Predictors of Cognitive Functioning Trajectories in Older Americans - Chodosh, Joshua (2010)
OBJECTIVES: The concurrent influence of depressive symptoms, medical conditions, and disabilities in activities of daily living (ADL) upon the rates of decline in older Americans’ cognitive function is unknown. DESIGN: This study examined a national sample of 6,476 adults born before 1924 to determine differences in cognitive function trajectories by prevalence and incidence of depressive symptoms, chronic diseases, and ADL disabilities. Cognitive performance was tested 5 times between 1993 and 2002 with a multifaceted inventory that we examined as a global measure (range: 0–35, standard deviation (SD) 6.00) and with word recall (range: 0–20, SD 3.84) analyzed separately. RESULTS: Baseline prevalence of depressive symptoms, stroke, and ADL limitations were each independently and strongly associated with lower baseline cognition scores, but did not predict future cognitive decline. Each incident depressive symptom was independently associated with 0.06 point reduction (95% confidence interval (CI):0.02–0.10) in recall score, incident stroke with 0.59 point reduction in total score (95% CI:0.20–0.98), each new basic ADL limitation with 0.07 point (95% CI:0.01–0.14) reduction in recall score and 0.16 point reduction in total score (95% CI:0.07–0.25), and each incident instrumental ADL limitation with 0.20 point reduction in recall score (95% CI:0.10–0.30) and 0.52 point reduction in total score (95% CI:0.37–0.67). CONCLUSION: Prevalent and incident depressive symptoms, stroke, and ADL disabilities contribute independently to reductions in cognitive functioning in older Americans, but do not appear to influence rates of future cognitive decline. Therefore, prevention, early identification, and aggressive treatment of these conditions may ameliorate the burdens of cognitive impairment.